Impact of thermophoresis on nanoparticle distribution in nanofluids - Mehdi Bahiraei (Results in Physics, 2017)
This research attempts to study the effects of particle migration on concentration distribution of the water-TiO2 nanofluid inside a circular tube. The scale analysis shows that thermophoresis can have an essential role on particle migration and consequently, on concentration distribution. Therefore, the concentration distribution of particles is obtained by considering the effects of thermophoresis, non-uniform shear rate, Brownian diffusion, and viscosity gradient. The results reveal that as the particles become larger, the concentration distribution becomes more non-uniform. Meanwhile, thermophoresis intensifies non-uniformity of concentration distribution and its effect is more noticeable at higher mean concentrations. Keywords: Nanofluids, Nanoparticles, Thermophoresis, Particle distribution, Scale analysis